Analisis Fenomenologi Terhadap Makna dan Realita - Moh Nadhir Mu’ammar (LP2M IAIN Palangka Raya, 2017)
Phenomenology is precisely this deepening of self consciousness, this restless search for what lies back of the objects in which we ordinarily and scientifically lose our attention, or as we now call it our intention. Phenomenology is not merely the theory that this is so, but the putting it into practice, the urge to explore its interminable vistas. As a discipline, it is distinct from but related to other keys in philosophy: such as ontology, epistemology, logics, and ethics. The discipline of phenomenology is defined by its domain of study, its methods, and its main results. This paper globally makes a try at exploring the history and varieties of phenomenology. Phenomenology has been practiced in various guises for centuries, but it came into its down in the early 20th century in the works of Husserl, Heidegger, Merleau-Ponty and others. Phenomenological issues of intentionality, consciousness, and first-person perspective have been prominent in recent philosophy of mind.